Demographic variation, reintroduction, and persistence of an island duck (Anas laysanensis). Issue 6 (11th July 2013) - Reynolds, Michelle H.; Weiser, Emily; Jamieson, Ian; Hatfield, Jeff S.
Abstract Population variation in life history can be important for predicting successful establishment and persistence of reintroduced populations of endangered species. The Laysan duck (Anas laysanensis) is an endangered bird native to the Hawaiian Archipelago that was extirpated from most islands after the introduction of mammalian predators. Laysan ducks were restricted to a single remote island, Laysan Island (4.1 km2), for nearly 150 years. Since the species is not known to disperse between distant Hawaiian Islands today, 42 wild birds from Laysan Island were translocated to another mammalian predator‐free low‐lying atoll (Midway Atoll; 6.0 km2) to reduce extinction risk. We explored how variation in demography influences establishment and longer‐term retention of genetic diversity (rare alleles) for reintroductions of this species. We observed dramatic differences in population growth between the source (λ = 1.18) and reintroduced (λ = 3.28) population. The number of eggs hatched at Midway Atoll was greater than at Laysan Island, however, we found no difference in hatching success (proportion of clutch hatched) between populations. Adult females produced 3 times as many fledglings per breeding year on Midway Atoll compared to Laysan Island. We estimated population abundance of both populations until 2010 and applied a Gompertz model with a Bayesian approach to infer density dependence, process variation, observation error, and carrying capacity for the Laysan Island and Midway Atoll populations. The carrying capacity from the Gompertz model for Midway Atoll (K = 883 ± 210 SD) was estimated to be greater than that of Laysan Island (K = 598 ± 76 SD). Translocations with small numbers of founders and no immigration can create population bottlenecks, leading to loss of genetic variation over time, and potentially reducing the reintroduced population's viability or its potential to serve as a source for future translocations. Therefore, we also assessed the probability of retaining rare alleles in an isolated reintroduced Laysan duck population using life history parameters observed from the Laysan Island and Midway Atoll populations; we concluded that additional founders are needed under scenarios using demographic estimates from both Laysan Island and Midway Atoll to retain either 90% or 95% of source population genetic diversity. © 2013 The Wildlife Society.